A STUDY OF STRESS MANAGEMENT AMONG STUDENTS DURING ONLINE EDUCATION IN KANIYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Stress can be defined as any type of change that causes physical, emotional orpsychological strain. Stress is our body's response to anything that requires attention oraction. Everyone experiences stress to some degree.Stress is a feeling of emotional orphysical tension. It can come from any event or thought that makes us feel frustrated, angry,or nervous.In short bursts, stress can be positive such as when it helps us avoid danger ormeet a deadline. But when stress lasts for a long time, it may harm our health.I try to find outthe impact of stress management among students in online classes. Also I have observed thevarious steps taken by them to avoid the stress to students amid. I collected the data’s throughprimary and secondary data and I give suggestions to the betterment of studies